Investigating associations between biting time in the malaria vector Anopheles arabiensis Patton and single nucleotide polymorphisms in circadian clock genes: support for sub-structure among An. arabiensis in the Kilombero valley of Tanzania. Issue 1 (December 2016) - Maliti, Deodatus; Marsden, C.; Main, B.; Govella, N.; Yamasaki, Y.; Collier, T.; Kreppel, K.; Chiu, J.; Lanzaro, G.; Ferguson, H.; Lee, Y.
Abstract Background There is growing evidence that the widespread use of Long-Lasting Insecticidal Nets (LLINs) is prompting malaria vectors to shift their biting towards times and places where people are not protected, such as earlier in the evening and/or outdoors. It is uncertain whether these behavioural shifts are due to phenotypic plasticity and/or ecological changes within vector communities that favour more exophilic species, or involve genetic factors within vector species to limit their contact with LLINs. Possibly variation in the time and location of mosquito biting has a genetic basis, but as yet this phenomenon has received little investigation. Here we used a candidate gene approach to investigate whether polymorphisms in selected circadian clock genes could explain variation in the time and location of feeding (indoors versus outside) within a natural population of the major African malaria vectorAnopheles arabiensis . Methods Host-seekingAn. arabiensis were collected from two villages (Lupiro and Sagamaganga) in Tanzania by Human Landing Catch (HLC) technique. Mosquitoes were classified into phenotypes of "early" (7 pm–10 pm) or "late" biting (4 am –7 am), and host-seeking indoors or outdoors. In these samples we genotyped 34 coding SNPs in 8 clock genes (PER, TIM, CLK, CYC, PDP1, VRI, CRY1, and CRY2 ), and tested for associations between these SNPs and biting phenotypes. SNPs in 8 mitochondrial genes (ATP6, ATP8, COX1, COX2, COX3, ND3, ND5 andCYTB ) were also genotyped to test population subdivision withinAn. arabiensis . Results The candidate clock genes exhibited polymorphism withinAn. arabiensis, but it was unrelated to variation in the timing and location of their biting activity. However, there was evidence of strong genetic structure withinAn. arabiensis populations in association with theTIM, which was unrelated to geographic distance. Substructure withinAn. arabiensis was also detected using mitochondrial markers. Conclusions The variable timing and location of biting inAn. arabiensis could not be linked to candidate clock genes that are known to influence behaviour in other Diptera. This finding does not rule out the possibility of a genetic basis to biting behaviour in this malaria vector, but suggests these are complex phenotypes that require more intensive ecological, neuronal and genomic analyses to understand.